2011
DOI: 10.1088/0253-6102/56/2/34
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological Models with Fractional Derivatives and Fractional Action Functional

Abstract: Cosmological models of a scalar field with dynamical equations containing fractional derivatives or derived from the Einstein-Hilbert action of fractional order, are constructed. A number of exact solutions to those equations of fractional cosmological models in both cases is given.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 27 publications
0
64
0
Order By: Relevance
“…As well known, the fractional action cosmology (FAC) is the new field of research based on the principles and formalism of the fractional calculus applied to cosmology. In this paper, we present the results of study of some exact models in FAC constructed by the author on the basis of the fractional action functional in [1]. These models are followed from the fractional variational principle for the dynamical field theories in general and the theory of gravity formulated by El -Nabulsi (see, e.g., [2], [3] and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well known, the fractional action cosmology (FAC) is the new field of research based on the principles and formalism of the fractional calculus applied to cosmology. In this paper, we present the results of study of some exact models in FAC constructed by the author on the basis of the fractional action functional in [1]. These models are followed from the fractional variational principle for the dynamical field theories in general and the theory of gravity formulated by El -Nabulsi (see, e.g., [2], [3] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we aim to develop further the FAC model proposed by the author in [1] and obtain the new exact solutions to this model. Exact solutions of the modified Friedmann equations in FAC are important to analyze the possible behavior of these models in aspect of the accelerated cosmological expansion in aspect of the recent observational data.…”
Section: Introductionmentioning
confidence: 99%
“…• The ordinary time derivatives of the Friedmann equations of homogeneous and isotropic cosmology were replaced by fractional derivatives in [47][48][49][50]. In particular, in [50] it was shown that supernovae data on the late-time acceleration of the universe can be explained by fractional Friedmann equations with derivative order close to 3/2.…”
Section: (γ−1) Cmentioning
confidence: 99%
“…Recently, a class of phenomenological models based on the concept of fractional calculus of variations, which is called the fractional action cosmology (FAC) has been proposed by El-Nabulsi [20]- [23]. Later, we significantly improved and developed these models in our works [24] - [26]. Our models are built on the…”
Section: Introductionmentioning
confidence: 99%